Les faunes de coraux (Anthozoaires Scléractiniaires) de la façade atlantique française au Chattien et au Miocène - Cahuzac, B. (2010)
The study of new abundant coral crops and a systematic revision of the historie collections allow us to extend significantly the data about the Upper Oligocene and Miocene Scleractinia of the French atlantic basins. The SW and W-NW France faunas have been considered, and complete lists of the different defined taxa are presented. The general lines of the evolution of this group are specified, and linked to the paleoclimatic and paleobiogeographic changes.